Pa Jinglebob : the fastest knitter in the west - "Arrigan, Mary" (Egmont: London, 2002)
When Not-Nice Nellie and her bandits hit the town of Buckaroo, Jemima begins to wish her gentle Pa hadn't been made Sheriff. But at least Pa Jinglebob is the fastest knitter in the West! Suggested level: primary